Impairment of neuronal activity in the dorsolateral prefrontal cortex occurs early in parkinsonism - Hjelle, Noah; Mohanty, Biswaranjan; Hubbard, Tanner; Johnson, Matthew D.; Wang, Jing; Johnson, Luke A.; Vitek, Jerrold L. (Frontiers in Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is often characterized by altered rates and patterns of neuronal activity in the sensorimotor regions of the basal ganglia thalamocortical network. Little is known, however, regarding how neuronal activity in the executive control network of the brain changes in the parkinsonian condition.ObjectiveInvestigate the impact of parkinsonism on neuronal activity in the dorsolateral prefrontal cortex (DLPFC), a key region in executive control, during a go/nogo reaching task.MethodsUsing a within-subject design, single and multi-unit neuronal activity was recorded in the DLPFC of a nonhuman primate (n = 1) before and after the induction of mild parkinsonism using the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP).ResultsCoincident with development of mild parkinsonian motor signs, there was a marked reduction in the percentage of DLPFC cells with significant task-related firing rate modulation during go and nogo conditions.ConclusionThese results suggest that DLPFC dysfunction may occur early in parkinsonism and contribute to cognitive impairments and disrupted executive function often observed in PD patients.